The Olin experiment [engineering education experiment]. - Guizzo, E.
This paper describes the engineering education experiment conducted at the Franklin W. Olin College in Needham, MA, aimed at increasing the quality and quantity of the engineering workforce in the US. Instead of the usual theory-heavy lectures, segregated disciplines, and individual efforts, the experiment emphasizes design exercises, interdisciplinary studies and teamwork. Olin's radically new way of training engineers incorporates changes that many in industry and academia say are long overdue. Judging by some of their internships, it appears that Olin's first graduates will have no problems landing their desired jobs. Meanwhile, people are keeping an eye on these graduates as they make their way into the real world.
Keywords: Franklin W. Olin College; Bioinspired designs; Design exercises; Engineer training; Engineering education experiment; Engineering workforce; Interdisciplinary studies; Internships; Teamwork; Technological innovations